Desempenho alimentar e crescimento de recém-nascidos pré-termo submetidos à estimulação sensório motora oral - Bauer, Magda Aline (2008)
Abstract 1: Purpose: To review the scientific literature on oral-motor-sensorial stimulation in preterm infants, assessing its effects on feeding performance of this infants. Data sources: The data was obtained in scientific publications web sites of health fields, mainly in the last five years, approaching oral stimulation, nutritive (NS) and non-nutritive (NNS) sucking. Updated and relevant articles were searched. 25 articles, 1 dissertation and 4 book chapters were selected. Data synthesis: Presentation of the different stimulation methods and the efficiency comparison of each; the stimulation benefits in the sucking pattern, feeding performance, transition time from tube to oral feeding, length of hospital stay and the gain of weight during this period. Conclusion: Based on the reviewed articles it is possible to conclude that the SMO brings benefits to the preterm infants and, for the other hand, it doesn’t implied in adverse effects. The main benefits were due to sucking patterns progression, an improvement in the feeding performance, a shorter transition time from tube to oral feeding and a shorter hospital stay. Abstract 2: Purpose: the hypothesis that the sensory-motor-oral (SMO) stimulation could enhance the oral feeding performance of preterm infants has leaded this study. Thus, the purpose was to assess whether the SMO stimulation influences the preterm infants feeding performance. Methods: this was an analytic, intervention, controlled clinical trial type research. Twentyfour preterm infants were randomly placed into experimental (EG) and control (CG) groups. The experimental group received a sensory-motor-oral stimulation applied for 15 minutes before the feeding offer, twice a day. The stimulation was administered since they reached a 80 cal/kg/day enteral diet until the full oral feeding achievement. The results were analyzed by the STATA 10 software, and the groups were compared through the Independent TStudent Test (p < 0,05). Results: the groups didn’t differ about gender, gestational age and birthweight. At the first day of oral feeding, the experimental group demonstrated a greater rate of milk transfer, been the EG’s performance 2.03 ml/min (+/-1.41) X 1.35ml/min (+/- 0.97) in the CG; and the EG’S transfer tax 37.16 % (+/- 22.97) X CG’s 18.1 % (+/- 14.71) – this was a statistically significant difference. The necessary days to achieve full oral feedings were similar for both groups. However, 83% of the preterm infants who had the transition up to a week were stimulated, and 61% who took more than a week did not receive stimulation. For the group that had the early transition, the feeding performance was superior during the whole first week of oral feeding. The transition from tube to oral feeding took in average 5.16 days (+/- 1.33) to those infants that had an early transition and 11.94 days (+/- 3.28) in average to the others, a statistically significant difference. Conclusion: the SMO stimulation program enhanced the feeding performance of preterm infants, especially who did the transition from tube to oral feeding until seven days. Abstract 3:Purpose: to verify the sensory-motor-oral (SMO) stimulation program influence on the growth (weight, height and cranial perimeter); on the transition time and hospital stay length of preterm infants, once it is considered that the oral stimulation supports the feeding transition with no impairments to the physical growth of preterm infants. Methods: this was an analytic, intervention, controlled clinical trial type research. Twentyfour preterm infants were randomly placed into experimental (EG) and control (CG) groups. The experimental group received a sensory-motor-oral stimulation applied for 15 minutes before the feeding offer, twice a day. The stimulation was administered from when they reached enteral diet of 80 cal/kg/day until the full oral feeding achievement. The preterm infants were assisted concerning: gestacional age, days of life, days necessary to transition from tube to oral feeding, length of hospitalization and anthropometric measurements (weight, cranial perimeter and height). The results were analyzed by the STATA 10 software, and the groups were compared through the Independent T-Student Test (p < 0.05). Results: the preterm infants did no differ concerning days of life and anthropometric measurements at any point of the study, neither concerning the hospital stay length. The EG took the full transition 1.6 days before the CG, in average; not a statistically significant difference. However, when considering the transition time, it was depicted that the preterm infants who had the transition between 0-7 days were primarily from the EG (p=0.059).The infants who perform the transition earlier needed 5.16 days (+/- 1.33) in average to achieve the oral feeding, while the others needed 11.94 days (+/- 3.28). This was a statistically significant difference. Conclusion: The influence of SMO stimulation on the preterm infants’ growth and hospital release could not be observed. Concerning the length of stay, we observed that most of preterm infants whom took less time to do the transition from tube to oral feeding were from experimental group. So, the stimulation did not compromise the preterm infants’ growth and enhanced the transition from tube to oral feeding, and the latter demanded, in average, 6.78 less days to achieve full transition.